Assessment of Gene Flow to Wild Relatives and Nutritional Composition of Sugarcane in Brazil - Bressan, Eduardo Andrade; Carvalho, Igor Araújo Santos de; Borges, Maria Teresa Mendes Ribeiro; Carneiro, Monalisa Sampaio; Silva, Edson Ferreira da; Gazaffi, Rodrigo; Shirasuna, Regina Tomoko; Abreu, Vinícius; Popin, Rafael V.; Figueira, Antonio; Oliveira, Giancarlo Conde Xavier (Frontiers in Bioengineering and Biotechnology, 2020)
The commercial release of genetically modified organisms (GMO) requires a prior environmental and human/animal health risk assessment. In Brazil, the National Biotechnology Technical Commission (CTNBio) requires a survey of the area of natural occurrence of wild relatives of the GMO in the Brazilian ecosystems to evaluate the possibility of introgressive hybridization between sexually compatible species. Modern sugarcane cultivars, the focus of this study, derive from a series of hybridization and backcrossing events among Saccharum species. The so-called “Saccharum broad sense” group includes around 40 species from a few genera, including Erianthus, found in various tropical regions, particularly South-Eastern Asia. In Brazil, three native species, originally considered to belong to Erianthus, were reclassified as S. angustifolium (Nees) Trin., S. asperum (Nees) Steud., and S. villosum Steud., based on inflorescence morphology. Thus, we have investigated the potential occurrence of gene flow among the Brazilian Saccharum native species and commercial hybrids as a requisite for GMO commercial release. A comprehensive survey was carried out to map the occurrence of the three native Saccharum species in Brazil, concluding that they are sympatric with sugarcane cultivation only from around 14°S southwards, which precludes most Northeastern sugarcane-producing states from undergoing introgression. Based on phenology, we concluded that the Brazilian Saccharum species are unable to outcross naturally with commercial sugarcane since the overlap between the flowering periods of sugarcane and the native species is limited. A phylogenomic reconstruction based on the full plastid genome sequence showed that the three native Saccharum species are the taxa closest to sugarcane in Brazil, being closer than introduced Erianthus or Miscanthus. A 2-year study on eight nutritional composition traits of the 20 main sugarcane cultivars cultivated in Brazil was carried out in six environments. The minimum and maximum values obtained were, in percent: moisture (62.6–82.5); sucrose (9.65–21.76); crude fiber (8.06–21.03); FDN (7.20–20.68); FDA (4.55–16.90); lipids (0.06–1.59); ash (0.08–2.67); and crude protein (0.18–1.18). Besides a considerable amount of genetic variation and plastic responses, many instances of genotype-by-environment interaction were detected.